2000
DOI: 10.1128/jb.182.18.5046-5051.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrogen Peroxide-Forming NADH Oxidase That Functions as an Alkyl Hydroperoxide Reductase in Amphibacillus xylanus

Abstract: The Amphibacillus xylanus NADH oxidase, which catalyzes the reduction of oxygen to hydrogen peroxide with ␤-NADH, can also reduce hydrogen peroxide to water in the presence of free flavin adenine dinucleotide ( We have reported previously on a new group of facultatively anaerobic bacteria isolated from alkaline compost (17). Since the bacteria have unique phenotypic and chemotaxonomic characteristics (18), as well as bioenergetic properties (13), we named one of the isolate Amphibacillus xylanus (18). A. xylan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…Precedents for reduction of exogenous flavins by flavoproteins exist, including the reductase modules of two-component monooxygenases (reviewed in ref. 27) and an Amphibacillus xylanus NADH oxidase (28). Although the capacity for electron transfer between flavoproteins and exogenous flavins in vitro appears to be a general phenomenon (24), its physiological implications in the present case are less clear.…”
Section: Discussionmentioning
confidence: 42%
“…Precedents for reduction of exogenous flavins by flavoproteins exist, including the reductase modules of two-component monooxygenases (reviewed in ref. 27) and an Amphibacillus xylanus NADH oxidase (28). Although the capacity for electron transfer between flavoproteins and exogenous flavins in vitro appears to be a general phenomenon (24), its physiological implications in the present case are less clear.…”
Section: Discussionmentioning
confidence: 42%
“…Comparison of P. putida AhpC with corresponding protein from S. typhimurium , Xanthomonas campestris pv. phaseoli (Loprasert et al, 1997), P. aeruginosa (Stover et al, 2000) and Amphibacillus xylanus (Niimura et al, 2000) showed 69, 66, 65, and 65% overall similarity, respectively (data not shown). Two highly conserved cysteine residues among bacterial AhpCs are found at 47 and 166.…”
Section: Molecular Cloning Of Ahpc and Ahpfmentioning
confidence: 99%
“…The enzymes catalyze the reduction of oxygen by NADH to form hydrogen peroxide. However, in the presence of a 21-kDa disulfide-containing redox protein (AhpC), now commonly referred to as peroxiredoxin (Prx), the NADH oxidases also showed extremely high reductase activity for both hydrogen peroxide and alkyl hydroperoxides (26,(28)(29)(30). These NADH oxidases thus belong to a growing new family of peroxiredoxin oxidoreductases (PrxR) (38) and are involved not only in the regeneration of NAD but also in the removal of peroxides.…”
mentioning
confidence: 99%